Analisis Studi Kelayakan Bisnis Produk Kasa di CV. Payung Global Kota Tasikmalaya - Ernawati; Hani Nabillah; Fitriani Fatmawati (LPPM Sekolah Tinggi Teknologi Cipasung, 2022)
CV. Payung Global is a company that produces health support equipment such as gauze. There is a company's desire to conduct a business feasibility study to gauze products to find out and fix problems such as production delays, so it is necessary to analyze a business feasibility study by analyzing legal aspects, marketing aspects, environmental aspects, management, and HR aspects, technical aspects and financial aspects which are analyzed by this method. payback period (PP), net present value (NPV), profitability index (PI), Break event point (BEP), and internal rate of return (IRR). Based on information from the company, the increase in demand reaches 20% per year, but the supply capacity is still limited. So it is necessary to analyze the business feasibility of gauze products. The results of the analysis in terms of the market aspect, namely the gauze product business has good market opportunities in Tasikmalaya. Technical aspects, aspects of production capacity according to sales targets with facilities that support the business. The aspect of HR has an organizational structure with sufficient manpower. Legal and environmental aspects, the gauze product business is legal and complies with applicable permits and the gauze production process does not have an environmental impact because it does not produce waste. The financial aspect, a payback period of 6 months 23 days, Net Present Value is positive Rp.1,824,400,000 and Internal Rate of Return is greater than MARR which is 10.3%.